Science and Polity in France : The End of the Old Regime - Gillispie, Charles Coulston (Book collections on Project MUSE., 2004)
By the end of the eighteenth century, the French dominated the world of science. And although science and politics had little to do with each other directly, there were increasingly frequent intersections. This is a study of those transactions between science and state, knowledge and power--on the eve of the French Revolution. Charles Gillispie explores how the links between science and polity in France were related to governmental reform, modernization of the economy, and professionalization of science and engineering.